Physical and rheological properties of red tilapia (Oreochromis niloticus linnaeus) mince for development of spray-dried fish powder - Uzzaman, Md Akhter (2012)
In order to examine the potential of utilizing whole mince of red tilapia (Oreochromis niloticus) powder as surimi or surimi based products, the effect of various additives such as potato starch (PS) (5-25%), sago starch (SS) (5-25%), chitosan (0.4-2.0%) and sodium tripolyphophate (TPP) (0.05-1.0%) on the gelation related properties as well as on the thermal and rheological behavior were evaluated. The most promising additive for improving tilapia mince meat gelation properties was identified and the tilapia slurry was then spray dried and optimization was carried out using response surface methodology. The effect of inlet and outlet temperatures and maltodextrin concentration on the gelling capacity, colour, moisture content and water activity of the fish powder were determined. The texture and colour properties of tilapia mince paste was improved by the addition of chitosan>potato starch>sago starch>TPP. More elastic gel was obtained in kamaboko type gel containing 0.4% chitosan. For directly heated gels, gel with 1.2% chitosan exhibited the highest springiness property, followed by 10% potato starch. Harder gels were obtained for PS or SS compared to chitosan and TPP. Chitosan at 0.4% produced kamaboko gel with higher L* value (lightness), low b* value (yellowness) and higher whiteness index compared to others. Similar effect by chitosan was recorded in directly heated gels for 0.8% and 1.6% incorporation. The presence of starch and/or TPP either decreased or did not have any effect on the lightness, yellowness or whiteness values of gels. The differential scanning calorimetry (DSC) trace of tilapia mince paste showed two zones of sharp endothermal effects with Tmax of 52.2°C and 68.48 °C for the thermal denaturation of myosin and actin, respectively. The addition of 20-25% PS and 15% SS in tilapia mince resulted in thermal stability of myosin but not affecting actin. Starch addition significantly ( p< 0.05) lowered the denaturation temperature of myosin. The tilapia mince paste without additive exhibited good elastic properties with high value of G¢ (6.6 kPa) and was further enhanced by the addition of the additives. The additive incorporated tilapia mince complex had G'>G''. Storage moduli (G') increased with 5- 10% PS and 20-25% SS, whereas the elastic behavior of tilapia mince paste could also be improved by the addition of 0.05% TPP and 0.4% chitosan. Chitosan at 0.4% was chosen as the best additive for the production of tilapia meat powder. For spray drying, fish meat slurry was prepared with 0.4% Chitosan, 5 mM Calcium chloride, NaHCO3 and 5% w/w sorbitol.The optimized spray-drying conditions were found to be at the inlet temperature of 181.15°C and outlet temperature of 98.45°C with addition of 27.64% maltodextrin. The predicted optimum value of multiple response under optimal conditions were the least gelation concentration at 8.55%; whiteness at 88.19, moisture content at 2.65%, and water activity at 0.21 with a desirability function value of 0.885. The produced powder had whiteness value of approximately 97.69% moisture content of 2.63 gelling capacity at 8.67 and water activity of 0.255. The Spray-dried tilapia mince powder produced under the optimized conditions were evaluated for their storage stability at 4°C, 10°C, 30°C, 40°C and 60°C for a period of three months. The half-life of the spray-dried tilapia powder kept at 10°C, ambient temperature (30±2°C) and at 40°C were predicted to be approximately fourteen months, five months and two and half months, respectively.